The timing of new corporate debt issues and the risk-return tradeoff - Koutmos, Dimitrios; Bozos, Konstantinos; Dionysiou, Dionysia; Lambertides, Neophytos (My University, 2018)
The Modigliani–Miller theorem serves as the standard finance paradigm on corporate capital structure and managerial decision making. Implicitly, it is assumed that the market possesses full information about the firm. However, if firm managers have insider information, they may attempt to ‘signal’ changes in the firm’s financial structure and, in competitive equilibrium, shareholders will draw deductions from such signals. Empirical work shows that the value of underlying firms rises with leverage because investors expect such firms to implement positive NPV projects. We empirically examine this view using a sample of debt issue announcements by publicly traded firms listed on the London Stock Exchange. We argue that the timing of debt issues is fundamental in determining the relationship between leverage and risk-adjusted returns. We show that an announcing firm’s intrinsic value may not rise depending on when management publicly ‘signals’ changes in their firm’s capital structure. Specifically, we show that risk-adjusted returns rise positively for firms that make debt announcements during normal economic conditions while they tend to decline for firms making debt announcements during recessionary periods. During recessionary periods, market risk and loss aversion rise and investors focus less on the potential growth of debt announcing firms and focus more on potential losses instead. We conclude that the timing of new debt is of paramount importance and managers’ inability to prudently time such announcements can lead to exacerbated levels of systematic risk coupled with a significant erosion in shareholder wealth.
Keywords: Bivariate EGARCH; Debt announcements; Modigliani–Miller; Risk-return tradeoff